2009
DOI: 10.1055/s-0029-1185797
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ischemic Activity and Endothelium-Dependent Vasorelaxant Effect of Hydrolysable Tannins from the Leaves ofRhus coriaria(Sumac) in Isolated Rabbit Heart and Thoracic Aorta

Abstract: The aim of this work was to investigate the cardioprotective activity of hydrolysable gallotannins from Rhus coriaria L. leaves extract (RCLE) in isolated rabbit heart preparations, submitted to low-flow ischemia/reperfusion damage. RCLE induces a dose-dependent normalization of coronary perfusion pressure (CPP), reducing left ventricular contracture during ischemia, and improving left ventricular developed pressure and the maximum rate of rise and fall of left ventricular pressure at reperfusion. Creatinine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 23 publications
2
52
0
Order By: Relevance
“…Sumac contains various substances and exactly tannin and gallic acids may be responsible for the antioxidant ability of this plant. It was reported that the antioxidant activity of gallotannins from R. coriaria L. leaves’ extract was stronger than that of gallic acid (Beretta et al., 2009). Tannic acid extracted from Rhus chinensis Mill.…”
Section: Antioxidant Status Of Rabbitsmentioning
confidence: 99%
“…Sumac contains various substances and exactly tannin and gallic acids may be responsible for the antioxidant ability of this plant. It was reported that the antioxidant activity of gallotannins from R. coriaria L. leaves’ extract was stronger than that of gallic acid (Beretta et al., 2009). Tannic acid extracted from Rhus chinensis Mill.…”
Section: Antioxidant Status Of Rabbitsmentioning
confidence: 99%
“…PGG (purity > 98%) was obtained by semi‐preparative HPLC from a MeOH/H 2 O extract of Rhus coriaria L. (Anacardiaceae) as previously described 12. To investigate the dynamic behavior of PGG, three independent molecular dynamic simulations were done, in water, DMSO and hydrated bilayer.…”
Section: Experimental and Computationmentioning
confidence: 99%
“…Besides these effects, PGG has anti‐diabetic and anti‐obesity properties through inhibition of adipocyte differentiation and stimulation of glucose uptake through insulin‐mimicking activity 10. In addition, there are reports of gastroprotective activity by inhibition of gastric H + , K + ‐ATPase,11 a cardioprotective effect against ischemia‐reperfusion damage in isolated rabbit heart and aorta12 and antithrombotic action 13…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confi rmed a correlation between the consumption of foods rich in ellagitannins (walnuts, pomegranates) and improved cardiovascular health [Beretta et al 2009, Larossa et al 2010.…”
Section: Introductionmentioning
confidence: 99%